EFEKTIFITAS MIKROORGANISME LOKAL (MOL) LIMBAH BUAH-BUAHAN SEBAGAI AKTIFATOR PEMBUATAN KOMPOS - Ali, Haidina (JURNAL MEDIA KESEHATAN, 2016)
Constraints or public complaints in the process of composting organic wastelies in the composting process that takes a long time between 2-3 months and acceptanceof people who are less fit to existing activator as EM4 scarce in Rural. The purpose of thisstudy was to determine the effectiveness of the Local Microorganisms activator (MOL)waste fruits of the length of time the formation of compost organic waste. This type ofresearch is an experimental design using "posttest with control". The results of the studythe average length of time (days) composting organic waste with the addition of MOLactivator dose of 10 mL for 24 days, a dose of 15 ml for 18.6 days, a dose of 20 mL for 15days, and a dose of 25 ml for 11.6 days. The addition of MOL activator with a dose of 25mL is the most effective dose in composting organic waste. Obtained p = 0.000 <α = 0.05;there were significant differences between the old time of the formation of the addition ofcompost activator Local Microorganisms (MOL) at a dose of activator 10 mL, 15 mL, 20mL and 25 mL. Expected research MOL activator use in composting organic waste can bea solution, especially for people in overcoming the problem of composting which takes along time.